ANALYSIS OF FINANCIAL PERFORMANCE AT PT. TELKOM INDONESIA Tbk. PERIOD 2019-2023: ANALISIS KINERJA KEUANGAN PADA PT. TELKOM INDONESIA Tbk. PERIODE 2019-2023 - Swargo Mulya, Tegar (International Journal of Economic Entrepreneurship and Business Management, 2024)
This research aims to find out and analyze how the financial performance of PT. Telkom Indonesia Tbk uses the ratio of Liquidity, Solvency, Profitability and Activity. The population and sample used in this study are the financial statements of PT. Telkom Indonesia Tbk for the 2019-2023 period. The type of research used is quantitative descriptive. Based on the results of the research from the liquidity ratio in 2019-2023, the results are not good. The solvency ratio is also not good. Based on the profitability ratio, the net profit margin shows good results because it is above industry standards, while the return on assets and return on equity can be said to be poor. In the activity ratio, judging from the working capital turnover, it has shown good results, while judging from the total asset turnover and receivable turnover over, the results are not good. Overall, the company's financial performance can be said to be not good because the average has not reached the industry standards that have been determined.